Efficacy of narrow band ultraviolet "B" on the treatment of lichen planus - Mira Abdelmalak Damuan Farg; Ashraf Hassan Mohammed Suleiman; Mohammed Abdelnaeem Salam; Zakaria Mowafy Emam Mowafy (Cairo : Mira Abdelmalak Damuan Farg, 2013)
This study was undertaken to evaluate the efficacy of NB-UVB versus topical corticosteroides in treatment of lichen planus. Thirty patients males and females, age ranged from 15-80 years they were randomly assigned into two groups of equal number complaining from exsissive degree of lichen, were participated in this study: patients in group (A) (Experemental group) received NB-UVB three times per week for 3 months while patients in group (B) (Control group) received topical corticosteroides two times per day for 3 months
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Surgery
Issued also as CD
Keywords: Lichen planus; NB-UVB; Topical corticosteroides